Design and development of automatic evaporation pan system for hydrological station / Hasanuddin Mohd Ibrahim - Hasanuddin , Mohd Ibrahim (2018)
One of the most common method in measuring evaporation is using evaporation pan. Traditionally the measurement of the evaporation is conducted manually. The automatic version of the evaporation pan measurement is not very common although many studies of using various mechanism have been carried out. In 2016, 4 units of automatic evaporation pan system has been installed at selected Department of Irrigation and Drainage Malaysia (JPS) Hydrological Stations. After 2 years of installation, the installed system is still facing some problems and deficiency that need to be improved and enhanced. Apart from that, the control mechanism of the automation process is carried out using remote terminal unit (RTU) with the built-in controller function which is normally expensive and is not commonly used for other JPS hydrological stations. This study is aimed to review and evaluate the existing automatic evaporation pan system installed in JPS besides developing new type of controller using programmable logic controller (PLC) to control the existing automation process. Methods used for the study are evaluation of the suitability, durability and reliability of the existing system components, data analysis between manual and automatic system and PLC program design using CX-Programmer software. The existing automatic evaporation pan system which adopts its own design shows high automation efficiency and less process errors although it contains 3.5% of higher water volume compared with the standard manual pan which is not connected to any parts. It is found also that all the components installed outdoors in the Malaysian tropical climate exposed to high tear and wear process. Thus, best quality and highly durable components and workmanships are required to increase the lifespan despite regular maintenance. Lastly, the PLC automation of evaporation pan has been successfully simulated using the real-time clock function and the instructions such as scaling and value comparison of the PLC CX- Programmer software.